GEOLOGY AND 3-D STATIC RESERVOIR MODELLING OF KURO FIELD, PARIGI FORMATION, JATIBARANG SUB-BASIN, NORTHWEST JAVA BASIN - Ilham, Muhammad
Kuro Field is one of field in Jatibarang Sub-basin, Northwest Java Basin that producing gas and located in Indramayu Regency, West Java Province and a work area of PT. Pertamina EP Asset 3. This research focused on Parigi Formatian in Kuro Field as a gas carbonate reservoir. The purposes of this research are to study about geological framework, determining 3-D model and distribution of reservoir properties, and estimate the value of Original Gas in Place (OGIP) in Kuro Field. Data used to achieve that purposes are wireline log from six wells, cutting description, 3-D seismic data, and well test data. Analysis conducted on stratigraphic correlation, facies and environment of deposition determination, and petrophysical analysis. Based on the cutting description, lithofacies in Kuro Field are packstone-grainstone and wackestone-packstone. The environment of deposition in this field is detached rimmed carbonate platform. Facies modelling conducted using Truncated Gaussian Simulation (TGS) method and divide facies into platform interior, platform margin reef, and slope while petrophysical properties modelled by Sequential Gaussian Simulation (SGS) method. The result of Original Gas in Place (OGIP) estimation in Kuro Field is 27 BSCF.